Electromagnetic Radiation from Mobile Phone near Ear-skull Region - Dayang Azra, Awang Mat; Kho, Franky; Joseph, Annie; Kuryati, Kipli; Shafrida, Sahrani; Kasumawati, Lias; Ade Syaheda Wani, Marzuki (IEEE, 2010)
Mobile phones produce radio frequency signal that is transferred as Electromagnetic radiation (EMR). EMR has the ability to penetrate through semi solid substances especially human body's tissues and caused dielectric heating. This effect can be classified as thermal and non thermal radiation. The skin near ear skull region is very thin compare to other part of human body. When using mobile phone for a longer period of time, this area absorbs EMR easily that can affects human immune systems. This effect resulted the increased of temperature near the ear skull region. Experimental study was conducted by using a volunteer to examine the effect of EMR produced by two different mobile phones with serving frequency of 900MHz and 1800MHz. This study was done in a laboratory for average of 45 minutes of talking time. Data is collected every 5 minutes using thermal imaging camera and thermal couples' probes. It is shown that temperature near the ear-skull region increased rapidly at the average of 2–4°C differences compare to before the used of mobile phone. When using adds in tools, the temperature rose more gradually and minimally. It is proven that the EMR would not cause any adverse effect towards human health such as cancer or tumor.